Co-expression and purification of the RadA recombinase with the RadB paralog from Haloferax volcanii yields heteromeric ring-like structures - Patoli, Bushra B.; Winter, Jody A.; Patoli, Atif A.; Delahay, Robin M.; Bunting, Karen A. (Society for General Microbiology, 2017)
The study of archaeal proteins and the processes to which they contribute poses particular challenges due to the often extreme environments in which they function. DNA recombination, replication and repair proteins of the halophilic euryarchaeon, Haloferax volcanii (Hvo) are of particular interest as they tend to resemble eukaryotic counterparts in both structure and activity, and genetic tools are available to facilitate their analysis. In the present study, we show using bioinformatics approaches that the Hvo RecA-like protein RadA is structurally similar to other recombinases although is distinguished by a unique acidic insertion loop. To facilitate expression of Hvo RadA a co-expression approach was used, providing its lone paralog, RadB, as a binding partner. At present, structural and biochemical characterization of Hvo RadA is lacking. Here, we describe for the first time co-expression of Hvo RadA with RadB and purification of these proteins as a complex under in vitro conditions. Purification procedures were performed under high salt concentration (>1 M sodium chloride) to maintain the solubility of the proteins. Quantitative densitometry analysis of the co-expressed and co-purified RadAB complex estimated the ratio of RadA to RadB to be 4 : 1, which suggests that the proteins interact with a specific stoichiometry. Based on a combination of analyses, including size exclusion chromatography, Western blot and electron microscopy observations, we suggest that RadA multimerizes into a ring-like structure in the absence of DNA and nucleoside co-factor.